A survey of V2X security protection technologies - Fuyuan CHEN; Zhenjiang DONG; Jiankuo DONG; Minjie XU (Dianxin kexue)
The vehicle-road-cloud collaborative V2X system has gradually become a national strategy, and the safety of V2X is related to driving security, life security, property security and even national security, which has increasingly become a hot spot for industry research.Firstly, the overall situation of the V2X security industry and the technology architecture of vehicle-road-cloud collaboration were introduced.Secondly, based on the “vehicle-road-cloud” technology system of V2X, the current status of domestic and international research was discussed, and the remaining problems and challenges in the field of V2X security protection were analyzed from three levels: V2X terminal security, roadside security and cloud security.Finally, the future development and research focus of the V2X security and protection technology were foreseen.